The Existence of Sharia Economic Law in the National Legal Order - Neng Yani Nurhayani; Oyo Sunaryo Mukhlas; Atang Abdul Hakim (Studi Multidisipliner: Jurnal Kajian Keislaman, 2026)
This research aims to analyze the existence of Sharia Economic Law in the national legal order in Indonesia. The research uses normative legal research methods by examining primary, secondary, and tertiary legal materials related to research problems. This study focuses on the existence of Sharia Economic Law in the national legal system, the principles of sharia economics, and the development of the sharia economy in Indonesia. Through this approach, this study provides a comprehensive overview of the position and role of Sharia Economic Law in the Indonesian legal system. The results of the study show that: (1) historically Sharia Economic Law has existed in Indonesia since the colonial period, although it is still in the early stages of development as an effort to confront the Dutch capitalist system. The establishment of banking institutions by Aria Wiraatmaja in 1898 became one of the initial solutions for national economic development which was substantively relevant to the concept of musharakah from the perspective of Islamic Economic Law; (2) the existence of Western Economic Law, especially treaty law that regulates the rights and obligations of the parties, has relevance to the theory of engagement in Sharia Economic Law so that Sharia Economic Law also functions as a reinforcement of existing law (li ta'kid); (3) Sharia Economic Law as a derivation of the religious beliefs of Muslims which is closely related to the concept of theology and muamalah occupies a position as part of efforts to formalize Islamic sharia into national law; and (4) the existence of Sharia Economic Law in the national legal system reflects the form of law obedience or the obedience of the Muslim community to God's law.